A warm and sympathetic thing: Voice and dysfluency in Robert Browning's 'Mr Sludge, "The Medium"'. Issue 2 (1st December 2020) - Martin, Daniel
This article takes a dysfluency studies approach to representations and expressions of voice and dysfluent speech in Robert Browning's minor dramatic monologue 'Mr Sludge, "The Medium"' (1864). Browning's speaker, an American spiritualist medium named Sludge, is vile and repugnant in his casuistry and sophistry as he defends his deceptions after being caught as a cheat during one of his séances. While Browning's contemporaries recognized 'Mr Sludge' as a mockery of the real-life American medium Daniel Dunglass Home, the monologue relies on one central metaphor of the medium's stuttering and stammering body that challenges broader Victorian assumptions about the relationship between speech, voice and elocutionary practices. Throughout this article, G.K. Chesterton's claim that Browning's critique of spiritualist practices is paradoxically a 'warm and sympathetic thing' becomes the keystone for understanding the monologue's contributions to modern thought about the pleasures and vitality of dysfluent speech. Fundamentally, Browning's exploration of the spiritualist's deceptions and conjuring of the voices of the dead reflects broader medical analogies beginning in the 1840s that linked the causes of dysfluent speech to invasive and contagious voicings.